Lactated Ringer's Vs Normal Saline for Acute Pancreatitis: : An Updated Systematic Review and Meta-Analysis - Aziz, Muhammad (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.